Implementation of the Stad Learning Model to Improve Civic Education Learning Outcomes in Elementary Schools - Nurafrisa, Luthfia (International Journal of Students Education, 2024)
This study aims to apply the STAD learning model so that teachers can create a learning environment that increases students’ attention to learning materials. In reality, some teachers prefer to apply conventional learning models. They often act as teachers, while students act as passive recipients of information with a traditional teaching style, which has more accurate information content. This learning model establishes teachers as the core of the continuity of the teaching and learning process. Students are considered to have the same interests, skills, learning interests and learning readiness. Students are not given many opportunities to express their opinions and discuss with other students. The research method used is the literature review method or literature review where this study seeks and collects previous research sources that are in accordance with the problems to be studied. This study discusses the application of the STAD learning model, as well as discussing the steps for implementing STAD by dividing groups, delivering materials, giving quizzes and also awarding achievements. With STAD learning outcomes, students are encouraged to actively exchange ideas with each other and understand a subject matter so that student learning outcomes can improve.